The management of loss : humanity's existential crises - Kets de Vries, Manfred F. R. (Routledge, 2026)
"Loss is experienced in many forms-from the death of a loved one, illness, and job loss, to the emotional turmoil surrounding retirement, divorce, separation, or even the quiet ache of boredom and loneliness. World-renowned leadership scholar, psychoanalyst, social psychologist, and executive coach Manfred Kets de Vries explores how we can navigate loss in both life and work. A pioneer in the field of clinical and psychodynamic-systemic executive coaching, Manfred examines a wide spectrum of losses-some obvious, others more subtle-shedding light on how we respond to them. Some people fight against loss, denying its reality at all costs. Others may become consumed by grief. For some, work becomes a coping mechanism, a way to manage the existential anxiety that stems from life's impermanence. In such cases, "manic" work habits can become a distraction-an escape from confronting painful truths. Written in an accessible and conversational style-as if speaking with a group of friends-this book offers deeply human insights brought to life through personal anecdotes, case studies, and illustrative vignettes. Manfred encourages readers to face their inner struggles without falling back on primitive defense mechanisms like splitting, projection, or denial. He guides us in reflecting on the consequences of our choices-past and future-so we may recognize our limitations, embrace our potential, and find meaning amid loss. An essential read for anyone grappling with loss, this book is especially valuable for executives, executive coaches, consultants, self-help enthusiasts, and well-being practitioners"-- Provided by publisher.
Keywords: Loss (Psychology); Grief.; elektronické knihy; electronic books